2020
DOI: 10.3390/ijerph17186741
|View full text |Cite
|
Sign up to set email alerts
|

Fear and Trembling of Cruise Ship Employees: Psychological Effects of the COVID-19 Pandemic

Abstract: The current COVID-19 pandemic has evolved to unprecedented proportions. This research aimed to gain a deeper understanding of the psychological effects of the COVID-19 pandemic on cruise ship employees stuck at sea. Using an inductive qualitative approach, a synchronous online focus group was conducted with nine cruise ship employees who were stuck at sea during COVID-19 pandemic. The findings revealed that COVID-19 pandemic has managed to erase the feeling of joy from cruise ship employees who were stuck at s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 55 publications
2
81
0
2
Order By: Relevance
“…Radic et al (2020) found the condition depression to be the case in their study coupled with poor human resource management strategies that lacked a contingency plan in managing health and epidemiologicaltype crisis such as the Covid-19, also bearing in mind that social isolation robustly contributes to depression (Alpert 2009;Radic et al 2020). The situation of maroon was pervasive and according to Dolven, close to 100, 00 cruise ship employees are stuck at sea for months (Dolven 2020;Radic et al 2020) due to the Covid-19 pandemic. K Whiting (2020), IMO, and the United Nations Conference on Trade and Development (UNCTAD) also suggested that as of mid-June, 300,000 seafarers per month needed scheduled international flights to enable crew change.…”
Section: The Covid-19 Virus and The Health Crises On The Maritime Indmentioning
confidence: 99%
See 3 more Smart Citations
“…Radic et al (2020) found the condition depression to be the case in their study coupled with poor human resource management strategies that lacked a contingency plan in managing health and epidemiologicaltype crisis such as the Covid-19, also bearing in mind that social isolation robustly contributes to depression (Alpert 2009;Radic et al 2020). The situation of maroon was pervasive and according to Dolven, close to 100, 00 cruise ship employees are stuck at sea for months (Dolven 2020;Radic et al 2020) due to the Covid-19 pandemic. K Whiting (2020), IMO, and the United Nations Conference on Trade and Development (UNCTAD) also suggested that as of mid-June, 300,000 seafarers per month needed scheduled international flights to enable crew change.…”
Section: The Covid-19 Virus and The Health Crises On The Maritime Indmentioning
confidence: 99%
“…Thus, they are interrelated, except under certain circumstance. Radic et al ( 2020 ), examining the psychological effect on employees of a cruise ship, reiterated that besides the direct health implication on contracting Covid-19, depression was a profound medical illness that negatively influences how an individual feels, thinks, and acts. Ultimately, it leads to sadness or deprivation of delight in previously pleasurable activities (Parekh, K n.().…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…When the COVID-19 Pandemic hit Indonesia, all human life sectors, like all other countries, experienced difficulties and sorrow (Putra et al, 2020;Hyder et al, 2020;Radic et al, 2020). There was no other choice at that time to reduce and break the pandemic chain; the Indonesian government was forced to take a policy by establishing a national Large-Scale Social Restriction.…”
Section: Introductionmentioning
confidence: 99%